Wandering Domains for Diffeomorphisms of the K-Torus: A Remark on a Theorem by Norton and Sullivan - Navas-Flores, A (Finnish Academy of Science and Letters, 2018)
We show that there is no Ck+1 diffeomorphism of the k-torus which is semiconjugate to a minimal translation and has a wandering domain all of whose iterates are Euclidean balls. © 2018 Annales Academiae Scientiarum Fennicae Mathematica.